The Role of SME in Improving Community Welfare: Study from Lara Village, Karossa Sub-District, Central Mamuju Regency, Indonesia - Nurhana, N.; Halim , Abdul; Dwi Saputra A , Jeffriansyah (Manunggal Halim Jaya, 2024)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (SME) in improving community welfare in Lara Village, Karossa District, Central Mamuju Regency. This research employs a qualitative approach, utilizing both primary and secondary data sources. The findings indicate that SME play a crucial role in enhancing the local economy. MSME actors contribute to sustaining the livelihoods of small-scale entrepreneurs and directly impact the living standards of lower-income communities, leading to overall improvements in welfare. The Lara Village Government supports MSME development by facilitating human resource training, business development programs, and providing assistance to business actors. Additionally, the village government plays a vital role in easing business operations and offering financial aid to support entrepreneurs in expanding their businesses. A key supporting factor in MSME development is the strong support from the village government. However, a significant challenge faced by SME in their efforts to improve community welfare is the limited availability of business capital, which hampers their growth and expansion.